Psychological factors of consumer behavior - Knysh, N. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
Consumer behavior might be considered as a kind of economic or social behavior, but, in any case, it bases on the psychological traits of the person and depend on his motivation. The last is a trigger in the decision-making process of particular product`s purchasing. That is why one of the main approaches in describing consumer behavior is psychoanalytic theory. In contrast to the rational theory of knowledge, psychoanalysis leaves room for the irrational decisions and momentary impulses that "It" provokes. Just remind sacral consumption — the belief that not only goods are acquired, but also a certain lifestyle, hopes for improving one’s own life and etc. In general, consumption is influenced by a number of factors, among which F. Kotler mentions: cultural factors, social, personal and psychological factors. The article describes the factors of internal and external influence on the behavior of consumers, the possibilities of their influence to direct the psychological factors of behavior in marketing activities and the main psychological aspects of consumer behavior and factors that determine the choice of a particular type of consumer behavior. The main groups of factors that influence the formation and implementation of consumer behavior are analyzed, special attention is paid to socio-psychological factors: social class (eight groups: the top of society, conservatives; dominant traditionalists; traditionally working class; dominant "new"; trendsetters; avant-garde; social "dependers"; poors), reference group, communication, social norms and values, personal lifestyle. There are examples of successful and unsuccessful marketing decisions of companies that, accordingly, account or ignored the needs of their consumers in the article. By the way, for Ukrainians, the main criteria for choosing a product are: price, brand and packaging, since the psyche of the consumer is not always aimed specifically at the product and, if products are more or less uniformity, the consumer will choose one, focusing not only on the specific differences of the goods, but also on their appearance.